1992
DOI: 10.1007/bf00200161
|View full text |Cite
|
Sign up to set email alerts
|

The thermochemical degradation of cork

Abstract: Summary.The thermochemical degradation of cork from Quercus suber L. was studied in the temperature range 150 ~ ~ in relation to mass loss, chemical composition and the influence on the cellular structure. The degradation of cork is strongly dependent on temperature and mass losses become significant at 200~ (15% of initial dry weight) and increase rapidly for higher temperatures (27% at 250 ~ 49% at 300 ~ 62% at 350 ~ until ashing at 450 ~ The polysaccharides are the most heat sensitive components: at 200 ~ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 14 publications
7
32
0
Order By: Relevance
“…This ratio (1/1.7) results from the higher S content of the MWL bamboo since S type phenols are set free easily. Additionally, the residual suberin in MCL, which is well known for its poor heat transfer and thermal stability (Pereira 1992), probably hampers the thermal volatilazation of MCL. Total hydrolysis of MCL could not be performed due to a lack of sufficient material.…”
Section: Analytical Pyrolysis and Analysis Of MCL And Lccmentioning
confidence: 99%
“…This ratio (1/1.7) results from the higher S content of the MWL bamboo since S type phenols are set free easily. Additionally, the residual suberin in MCL, which is well known for its poor heat transfer and thermal stability (Pereira 1992), probably hampers the thermal volatilazation of MCL. Total hydrolysis of MCL could not be performed due to a lack of sufficient material.…”
Section: Analytical Pyrolysis and Analysis Of MCL And Lccmentioning
confidence: 99%
“…The most important are: the grinding powder, from granulation or pre-grinding; the cleaning powder, without impurities; the finishing powder from cut and sanding operations or from cork disks and natural stoppers and finally the ''burning powder" that comes from the mixture of these powders [13]. The degradation of cork is strongly dependent on temperature and mass losses become significant at 200°C [14] and the colour start to change to dark brown and at 300°C to black [15]. At lower temperatures 75-85°C, only a phase transition was assigned to the melting of waxes present in cork obtained by DSC that was corroborated by dielectric spectroscopy [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the chemical degradation starts at about 250°C, in air, indicating that cork can be heated up to 250°C without inducing irreversible changes in its composition. Chemical methods [16,17] and scanning electron microscopy [16] were also applied and the results demonstrated that waxes and other soluble components of cork begin to decompose at ca. 150°C and that cork is transformed into ash for temperatures above 450°C.…”
Section: Introductionmentioning
confidence: 99%